2015
DOI: 10.7717/peerj.840
|View full text |Cite
|
Sign up to set email alerts
|

Association of academic stress with sleeping difficulties in medical students of a Pakistani medical school: a cross sectional survey

Abstract: Introduction. Medicine is one of the most stressful fields of education because of its highly demanding professional and academic requirements. Psychological stress, anxiety, depression and sleep disturbances are highly prevalent in medical students.Methods. This cross-sectional study was undertaken at the Combined Military Hospital Lahore Medical College and the Institute of Dentistry in Lahore (CMH LMC), Pakistan. Students enrolled in all yearly courses for the Bachelor of Medicine and Bachelor of Surgery (M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
142
4
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(185 citation statements)
references
References 24 publications
25
142
4
14
Order By: Relevance
“…In our study 117 (49%) were having poor sleep quality according to PSQI scale, this was similar to other studies conducted on medical students in Iran which showed 40.6% prevalence of poor sleepers, 38.9% in Brazil, 77% in Pakistan and in a study conducted on non-medical college students it was about 60%. [17][18][19][20] There was association between gender and sleep quality on univariate analysis with more boys among poor sleepers than among good sleepers, but on multivariate analysis it was not significant. In a study conducted by Ghoreishi et al on university medical students, out of total poor sleepers, 44.8% were male and 38% were female though the difference was not significant.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study 117 (49%) were having poor sleep quality according to PSQI scale, this was similar to other studies conducted on medical students in Iran which showed 40.6% prevalence of poor sleepers, 38.9% in Brazil, 77% in Pakistan and in a study conducted on non-medical college students it was about 60%. [17][18][19][20] There was association between gender and sleep quality on univariate analysis with more boys among poor sleepers than among good sleepers, but on multivariate analysis it was not significant. In a study conducted by Ghoreishi et al on university medical students, out of total poor sleepers, 44.8% were male and 38% were female though the difference was not significant.…”
Section: Discussionmentioning
confidence: 95%
“…17 In a study by Soni et al among adolescents, the mean (SD) global PSQI score was 10.75 (3.49), in a study by Waqas et al among medical students it was 8.1 (3.12) and in the present study it was 4.8 (2.49). 15,19 Those subjects who had high scores on SAS scale also had higher scores on PSQI scales, indicating high levels of poor quality of sleep among high users of smartphone. Positive and significant correlation was found between the SAS score and global PSQI score in a study conducted in Turkey with correlation coefficient (r) of 0.156 and in the present study it was 0.343.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, medical students in Chinese universities have more academic stress than other students and many have to shorten their sleep duration in order to meet the academic demands. 47 In addition, some studies found that psychological distress, anxiety, depression, and suicidality are relatively common in medical students, 48 which could increase the likelihood of short sleep duration. In contrast, long sleep (> 9 h/d) was more frequent in non-medical students than in medical students (9.9% versus 1.6%).…”
mentioning
confidence: 99%
“…Результати закордонних досліджень серед про-відних стресогенних чинників у студентів-медиків зазначають академічне навантаження (сurriculum workload [15], study pressure [16], academic performance [1,17]), особистісні проблеми та проб-леми комунікації мають меншу стресогенну дію. Специфіка причин та відсоток студентів з різним ступенем нервово-психічної напруги має деякі відмінності залежно від курсу навчання, що узго-джується з даними Dafaalla Mohamed та співавто-рів [18].…”
Section: досвід з організації навчальної роботиunclassified